2007
DOI: 10.1021/jf072707b
|View full text |Cite
|
Sign up to set email alerts
|

Structure Elucidation of a Pungent Compound in Black Cardamom: Amomum tsao-ko Crevost et Lemarié (Zingiberaceae)

Abstract: Natural plant extracts containing taste modifier compounds will gain more commercial interest in the future. Black cardamom, Amomum tsao-ko Crevost et Lemarié, used as a spice in Asia, produces a nice refreshing effect in the mouth. Therefore, an ethyl acetate extract was prepared, and constituents were separated by liquid chromatography. Guided by the tasting of each fraction (LC tasting), a new pungent compound was discovered, (+/-)-trans-2,3,3a,7a-tetrahydro-1H-indene-4-carbaldehyde. To confirm this new str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…(d) cis -2,3,3A,7A-Tetrahydro-1 H -indene-4-carbaldehyde ( 4 ) 53 : RI DB-WAX 1883. GC/MS m / z (%): 39 (13), 41 (9), 51 (11), 65 (13), 77 (26), 78 (8), 79 (10), 91 (100), 92 (25), 105 (35), 115 (11), 117 (13), 119 (50), 120 (16), 129 (7), 130 (12), 133 (7), 147 (11), 148 (53) [M] + .…”
Section: Methodsmentioning
confidence: 99%
“…(d) cis -2,3,3A,7A-Tetrahydro-1 H -indene-4-carbaldehyde ( 4 ) 53 : RI DB-WAX 1883. GC/MS m / z (%): 39 (13), 41 (9), 51 (11), 65 (13), 77 (26), 78 (8), 79 (10), 91 (100), 92 (25), 105 (35), 115 (11), 117 (13), 119 (50), 120 (16), 129 (7), 130 (12), 133 (7), 147 (11), 148 (53) [M] + .…”
Section: Methodsmentioning
confidence: 99%
“…Ester reduction yields the 1,3-cyclohexadienal scaffold, wherein relative configuration can be controlled by using different bases for the conjugated addition. This methodology has been used in the total synthesis of natural products containing 1,3-cyclohexadien-1-al scaffolds such as (±)-cis/trans-2,3,3a,7a-tetrahydro-1H-indene-4-carbaldehyde 61 and 63 that have been prepared starting from aldehyde 58 and the ylide of 59 [6]. Similar methodology has been applied for obtaining 1,3-cyclohexadienals due to their interest as intermediates of polysubstituted aromatic compounds, as indicated in the preparation of 67 from 64 and 65 Starting from linear starting materials, the cyclization to form six-membered rings can be performed in two steps through Horner olefination of α,β-unsaturated aldehydes and Michael addition to the resulting unsaturated system (Scheme 15).…”
Section: Aldol-type Reactions and Horner Olefinationsmentioning
confidence: 99%
“…This scaffold is present in natural products isolated from several plants [2,3], such as 2,6,6-trimethyl-1,3-cyclohexadien-1-carboxaldehyde known as safranal 2 that is the main constituent of the essential volatile oil of Crocus sativus L. (saffron) [4], or citral dimer 3, which has been isolated from marine bryozoan Flustra foliacea [5]. Some other examples are compound 5, extracted from black cardamom (Amomum tsao-ko) [6]; compound 6, which is obtained from the fungus Botrytis cinerea [7]; and compound 7 from an Indian fungi Parmelia perlata of Parmelia genus [8], which is used as a food supplement. Moreover several synthetic chiral structures such as compound 4 have been obtained [9] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Its fruits also have found applications in traditional Chinese medicine (TCM) for the treatment of stomach illness, digestive disorders, and throat infections [1]. Here we report on the isolation of a new bicyclononane aldehyde, (1RS,5SR,6RS)-5-hydroxybicyclo[4.3.0]non-2-ene-2-carbaldehyde (1), and 12 known compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) from the fruits of this species and on their antiproliferative activity in the murine neuroblastoma cell line N2a. The identification of a bicyclic aldehyde as active compound in a yeast-based screening for phosphoinositide-3 kinase (PI3K) inhibitors (unpublished results) led us to extend our search to other known sources of aldehydes, such as Amomum tsao-ko.…”
mentioning
confidence: 99%
“…A molecular formula of C 10 H 16 O 2 , identical with that of tsaokoin (3), was established on the basis of HR-ESI-MS ([M + Na] + , m/z = 189.0 902). Compounds 2-13 were identified as 6-hydroxyindan-4-carbaldehyde (2) [2], tsaokoin (3) [3,4], (2E,6E)-8-hydroxy-2,6-dimethyl-2,6-octadienal (4) [8], tsaokoarylone (5) [6], (2E,8E)-10-hydroxy-decadienal (6) [8], 4-hydroxy-benzaldehyde (7) [9], 4-methoxy-3-hydroxy-benzaldehyde (8) [9], (2E,6E)-8-hydroxy-2,6- [2,4,5]. The 1 H-and 13 C-NMR spectral data of 1 (l " Table 1) and tsaokoin (3) were only slightly different and suggested that 1 was an isomer of 3.…”
mentioning
confidence: 99%